Meta-analysis of global prevalence of hepatitis E virus infection in deer - Gao, Zhen-Qiu; Bao, Guang-Rong; Wang, Hai-Tao; Wei, Yong-Jie; Zhang, Miao; Tan, Wen-Xu; Liu, Hong-Lang; Zhao, Quan; Gong, Qing-Long; Jiang, Jing; Qin, Ya (Frontiers in Microbiology, 2025)
IntroductionHepatitis E virus (HEV) is an important zoonotic pathogen, and deer serve as a potential wildlife reservoir capable of contributing to human infections through wildlife–livestock–human transmission pathways. Accurate estimates of HEV prevalence in deer are essential for understanding zoonotic risks and informing surveillance strategies.MethodsWe conducted a systematic search across five major databases. Among 134 publications screened, 33 studies met the inclusion criteria for meta-analysis. Pooled prevalence estimates were calculated, and subgroup analyses were performed by region, development status, time period, age, sex, and diagnostic method. Serological assays (ELISA) and molecular assays (RT-PCR and RT-qPCR) were evaluated separately.ResultsSignificant geographical and demographic variation in HEV prevalence was observed. North America showed the highest pooled prevalence (29.57%, 95% CI: 0.00–89.25), with Mexico reporting the highest national estimate (62.68%, 95% CI: 54.54–70.47). Developing countries exhibited higher prevalence (21.45%, 95% CI: 7.12–40.63) than developed countries (5.01%, 95% CI: 2.40–8.43). HEV infection decreased over time, with lower prevalence after 2010 (4.92%, 95% CI: 1.57–9.83) compared with before 2010 (13.17%, 95% CI: 6.01–22.45). Adults had higher infection rates (23.02%, 95% CI: 9.04–41.06) than juveniles (10.11%, 95% CI: 5.83–15.41), and females slightly exceeded males (6.25% vs. 5.07%). Serology indicated past exposure (10.48%, 95% CI: 4.29–18.92), while molecular methods reflected active infection, with pooled rates of 8.58% for RT-PCR and 5.22% for RT-qPCR.DiscussionOur findings reveal substantial heterogeneity in HEV prevalence among deer and highlight the importance of standardized diagnostic protocols. These results underscore the need for harmonized surveillance to better assess zoonotic risks and support public health strategies targeting HEV transmission at the wildlife–human interface.